1990
DOI: 10.1161/01.atv.10.6.1051
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of coronary artery atherosclerosis by 17-beta estradiol in ovariectomized monkeys. Lack of an effect of added progesterone.

Abstract: Although controversy continues, the preponderance of evidence indicates that estrogen replacement therapy favorably influences the risk of coronary heart disease in postmenopausal women. It remains uncertain how this effect is mediated and whether the cyclic addition of a progestin may influence adversely an estrogenrelated cardioprotective effect. We investigated the influence of sex hormone replacement therapy on diet-induced coronary artery atherosclerosis in estrogendeficient (ovariectomized) adult female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
243
1
10

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(264 citation statements)
references
References 37 publications
10
243
1
10
Order By: Relevance
“…Despite the lack of a beneficial effect of CEE treatment on the plasma lipid profiles of the monkeys, there was a robust inhibition of the atherosclerosis progression (extent) and plaque severity/complications in all three main epicardial coronary arteries and the common iliac artery. That finding is comparable to a number of studies we have reported previously finding that estrogen treatment initiated immediately after making the monkeys surgically menopausal results is an average inhibition of about 70% in the progression of coronary artery atherosclerosis 21,25-27 . Interestingly, a similar estimate was made for the beneficial effects of estrogen treatment on the progression of carotid artery intimal media thickness of postmenopausal women 28 .…”
Section: Discussionsupporting
confidence: 90%
“…Despite the lack of a beneficial effect of CEE treatment on the plasma lipid profiles of the monkeys, there was a robust inhibition of the atherosclerosis progression (extent) and plaque severity/complications in all three main epicardial coronary arteries and the common iliac artery. That finding is comparable to a number of studies we have reported previously finding that estrogen treatment initiated immediately after making the monkeys surgically menopausal results is an average inhibition of about 70% in the progression of coronary artery atherosclerosis 21,25-27 . Interestingly, a similar estimate was made for the beneficial effects of estrogen treatment on the progression of carotid artery intimal media thickness of postmenopausal women 28 .…”
Section: Discussionsupporting
confidence: 90%
“…The administration of estrogens for prolonged periods inhibits the deposition of cholesterol in the arteries and thickening of the intima in monkeys and rabbits fed an atherogenic diet 8 . However, the mechanisms determining the direct effects of estrogens on the arterial wall have not been completely elucidated.…”
Section: Lipid Peroxidation and Nitric Oxide Inactivation In Postmenomentioning
confidence: 99%
“…19,27,46 Postmenopausal cynomolgus monkeys, like women, have reduced plasma concentrations of HDL cholesterol and increased amounts of coronary atherosclerosis compared with premenopausal females fed the same atherosclerotic diet for the same length of time. 47 Thus, both premenopausal and postmenopausal (ovariectomized) female cynomolgus monkeys share with women many of the same risk factors for the development of coronary artery disease. Furthermore, estrogen replacement therapy inhibits progression of coronary artery atherosclerosis, 47 suggesting that, like postmenopausal women, ovariectomized cynomolgus females respond similarly to hormone treatment.…”
Section: Cynomolgus Monkey Modelmentioning
confidence: 99%
“…47 Thus, both premenopausal and postmenopausal (ovariectomized) female cynomolgus monkeys share with women many of the same risk factors for the development of coronary artery disease. Furthermore, estrogen replacement therapy inhibits progression of coronary artery atherosclerosis, 47 suggesting that, like postmenopausal women, ovariectomized cynomolgus females respond similarly to hormone treatment.…”
Section: Cynomolgus Monkey Modelmentioning
confidence: 99%